Desarrollo de una aplicación web para la gestión de pacientes y personal médico de la clínica odontológica de la Universidad de las Américas - Izurieta Dueñas, Santiago Andrés (2017)
The present project arises from the need of the odonatological clinic of the University of the Americas to have a system that provides the facility to their students to schedule medical appointments. As well as automate the process of management of shifts by the teachers. The implementation of this system will improve the internal administrative process of customer service. The modules that were contemplated in the development of this software are: administration of students, administration of teachers, management of medical appointments, registration of patients, management of schedules for teachers. For the design and construction of the web system we used open source tools. To make the website we used the programming language php, java script and jquery. The database is implemented in MySQL. Also for this project we used the methodology of development PUD (Unified Process of Development). This allows developing the project in an iterative and incremental way. PUD is made to fit the wide variety of software system. So it was considered appropriate to implement it in our project to meet the time requirements we had to develop the system.